PETRIFIED WOOD OCCURRENCES IN WESTERN THRACE AND LIMNOS ISLAND: MINERALOGY, GEOCHEMISTRY AND DEPOSITIONAL ENVIRONMENT - Voudouris, P.; Velitzelos, D.; Velitzelos, E.; Thewald, U. (Bulletin of the Geological Society of Greece, 2007)
The present study describes the geology and mineralogy of the main petrified wood occurrences in Evros-Rhodopi and Limnos and integrates them in a volcanichydro thermal framework taking into consideration the nature of hydrothermal solutions during the silicification process. In the Lykofi-Fylakto-Lefkymi area, quartz and opal-CT are the main silica polymorph within the wood. The hostrocL· exhibit a zeolitic alteration suggesting reduced and slightly alkaline fluids for the silicification of wood. At Kassiteres/Sappes area the presence ofsilicified wood within kaolinite± alunite altered tuffbreccias indicates that slight acidic fluids were involved in the silicification processes. In Limnos Island the fossiliferous Portianou, Varos- Roussopouli and Moudros-Roussopouli areas occur in the periphery of an eroded volcanic edifice exposed at Fakos peninsula. The silicified wood occurs: (a) within weakly altered pyroclastics and (b) associated to several horizons of sinters interbedded within the pyroclastics. Transformation of amorphous silica to opal-CT and then to quartz is postulated based on XRD and SEM studies. The studied areas represent unique natural monuments, comparable to the petrified forest of Lesvos island.